Design, Construction and Testing of a Low Carbon Thin-Shell Concrete Flooring System. (April 2019) - Hawkins, Will; Orr, John; Shepherd, Paul; Ibell, Tim
Abstract: Rapid global urbanisation and population growth is driving unprecedented levels of building construction, with the total worldwide floor area expected to almost double over the next 40 years. Since most of the structural material in a building exists within the floors, these present a significant opportunity for structural engineers to contribute to a more sustainable construction industry. This paper examines a novel flooring system of textile-reinforced concrete shells with a foamed concrete fill, which has the potential to halve the amount of materials in a building's entire structure. A new design and geometry optimisation method is described, as well as the construction and testing of two prototypes; each 18 mm thick, 2 m in span and 200 mm tall. These textile-reinforced concrete shells are unconventional in their low total depth, low reinforcement content and lack of rigid supports. Both were reinforced with AR-glass fibre textile and constructed using fine-grained concrete, however only one featured a foamed concrete fill. Each was tested to destruction under an asymmetric load. In both cases, a hinged collapse mechanism was formed rather than sudden catastrophic failure, with positive implications for safety and robustness. A non-linear finite element model was developed which replicated the observed behaviour well, including cracking patterns. Inaccuracies in geometry arising from the hand-made construction methods were measured and their structural impact was assessed and found to be small. The investigations confirm the strength, robustness and buildability of the structural system, and establish a reliable analysis method. Graphical abstract: Unlabelled Image